(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Expansive soils causing significant damage to civil engineering structures. It has become a worldwide problem. In United States during 1973, the annual cost of damage was 2.3 billion due to expansive soil movement. A more up-to- date it has reached up to 9 billion annual damages to different structures. This paper presents experimental study of California bearing ratio values of soil-fly ash mixtures and randomly distributed Nylon fibres. The effect of addition of Nylon Fibres on California bearing ratio values (CBR) is studied. The percentage of HT Nylon 66 Fibres content is considered as 0.25 %, 0.75% and 1.25 % by stabilize soil- fly ash mixtures. Samples were cured in the laboratory under controlled conditions with optimum moisture content (OMC) and maximum dry density (MDD). The mathematical modelling is done to correlate California bearing ratio values with different parameters. The model is adequately useful to predict the strength. Adequacy has been tested by conducting different verification experiments on the developed model. It is found that difference of predicted and observed value is lying within 10%.